2013
DOI: 10.1007/s11427-013-4506-0
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and features of secondary metabolite biosynthetic gene clusters in Streptomyces ansochromogenes

Abstract: A draft genome sequence of Streptomyces ansochromogenes 7100 was generated using 454 sequencing technology. In combination with local BLAST searches and gap filling techniques, a comprehensive antiSMASH-based method was adopted to assemble the secondary metabolite biosynthetic gene clusters in the draft genome of S. ansochromogenes. A total of at least 35 putative gene clusters were identified and assembled. Transcriptional analysis showed that 20 of the 35 gene clusters were expressed in either or all of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…These cluster numbers are surprisingly high, and although many cannot be assigned to production of a certain metabolite, their abundance suggests that the genomes of these A. pullulans varieties represent rich resources for secondary metabolite biosynthesis. In comparison, antiSMASH predicted 45 T1 polyketide synthase/non-ribosomal peptide synthase/ dmat gene clusters in Penicillium chrysogenum , 29 clusters in Aspergillus fumigatus [66], and a total of 35 putative gene clusters in a draft genome sequence of Streptomyces ansochromogenes (Streptomycetes are known for their complex secondary metabolism) [67]. For example, lantipeptide biosynthetic clusters from A. pullulans var.…”
Section: Resultsmentioning
confidence: 99%
“…These cluster numbers are surprisingly high, and although many cannot be assigned to production of a certain metabolite, their abundance suggests that the genomes of these A. pullulans varieties represent rich resources for secondary metabolite biosynthesis. In comparison, antiSMASH predicted 45 T1 polyketide synthase/non-ribosomal peptide synthase/ dmat gene clusters in Penicillium chrysogenum , 29 clusters in Aspergillus fumigatus [66], and a total of 35 putative gene clusters in a draft genome sequence of Streptomyces ansochromogenes (Streptomycetes are known for their complex secondary metabolism) [67]. For example, lantipeptide biosynthetic clusters from A. pullulans var.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the corresponding gene cluster(s) responsible for the newly emerged bioactive compound(s) in ⌬adpA, we isolated the total RNA from both WT strain and ⌬adpA grown in MS, SP, and GP media at different time courses, respectively. Transcription of the core genes (27) in each PKS and NRPS secondary metabolic gene cluster in S. ansochromogenes genome was analyzed by reverse transcription-PCR (RT-PCR). The gene clusters silent in WT strain but activated in ⌬adpA are potentially responsible for the biosynthesis of the new bioactive compound.…”
Section: Activation Of a Cryptic Oviedomycin Biosynthetic Gene Clustementioning
confidence: 99%
“…Total RNA was isolated from S. ansochromogenes and its derivatives, and RT-PCR and qRT-PCR were performed as described previously (27,44).…”
Section: Rna Isolation Rt-pcr and Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Xi et al (2012) estimated that 27.5% of the isolates tested that belonged to the genus Streptomyces (34 isolates) showed antimicrobial activity, and it has been shown that the strains where both pks and nrps genes were identified produced a significantly higher number of secondary metabolites. Zhong et al (2013) demonstrated the assembly and features of secondary metabolite biosynthetic gene clusters with pks and nrps in S. ansochromogenes. In the current study, we provided evidence for the presence of both genes (nrps and pks) in the strain S. ansochromogenes TUR-10, suggesting that the production of the secondary metabolites might be performed by two metabolic routes.…”
Section: Discussionmentioning
confidence: 97%